2014
DOI: 10.3892/etm.2014.1497
|View full text |Cite
|
Sign up to set email alerts
|

Exercise upregulates salivary amylase in humans (Review)

Abstract: The secretion of salivary α-amylase is influenced by adrenergic regulation of the sympathetic nervous system and the hypothalamic-pituitary-adrenal axis; thus, exercise affects the levels of salivary α-amylase. Granger et al published a review in 2007 that focused attention on salivary α-amylase. In addition, a portable system for monitoring salivary α-amylase activity was launched in Japan at the end of 2005. The correlation between exercise and salivary α-amylase has since been extensively investigated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 18 publications
5
47
2
2
Order By: Relevance
“…Previous studies have indicated that the sAA levels of people who developed post-traumatic stress disorder (PTSD) following the East Japan earthquake decreased after taking care of plants (15 min/day) [55] and increased following exercise [62]. Similarly, in our current study, we found that the case group had reduced sAA levels after carrying out community garden activities despite no significant differences.…”
Section: Psychological Assessmentsupporting
confidence: 53%
“…Previous studies have indicated that the sAA levels of people who developed post-traumatic stress disorder (PTSD) following the East Japan earthquake decreased after taking care of plants (15 min/day) [55] and increased following exercise [62]. Similarly, in our current study, we found that the case group had reduced sAA levels after carrying out community garden activities despite no significant differences.…”
Section: Psychological Assessmentsupporting
confidence: 53%
“…Furthermore, the activity of this enzyme in saliva is affected by physical exercise, having a direct relationship with the exercise intensity. [112025] As for the psychological component, marked alterations in alpha-amylase levels were detected after applying stressors such as skydiving, academic tests, or stressful videos by different research groups[112627] that could be an explanation for our results because our study finished in period of academic exams.…”
Section: Discussionmentioning
confidence: 95%
“…However, since the production of sAA is regulated by the sympathetic nervous system (Rohleder and Nater 2009), exercise acutely enhances this activity substantially, especially at exercise intensities above 70 % of individual maximal oxygen uptake (Allgrove et al 2008;Koibuchi and Suzuki 2014). In this context, sAA activity correlates positively with plasma levels of catecholamine (Li and Gleeson 2004), anaerobic metabolism and blood lactate concentration (de Oliveira et al 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, assessment of sAA activity together with mood provides a reliable indicator of the exercise-induced psychological stress-response and mucosal immune function (Papacosta and Nassis 2011). While sAA activity rises acutely in connection with exercise (Allgrove et al 2008;Koibuchi and Suzuki 2014), it is expected to decrease chronically as intensive training progresses to chronic fatigue, impaired performance and non-functional overreaching (Papacosta and Nassis 2011). Thus, the question remains as to whether sAA activity and mood decrease when athletes are stressed by hypoxia in combination with high-intensity training for a prolonged period of time.…”
Section: Introductionmentioning
confidence: 99%